Gaming addiction and perceived stress among Saudi adolescents. (June 2020) - Rajab, Ahmad Mamoun; Zaghloul, Mohamed Saddik; Enabi, Saed; Rajab, Tawfik Mamoun; Al-Khani, Abdullah Murhaf; Basalah, Abdulrahman; Alchalati, Sara Wafik; Enabi, Joud; Aljundi, Saadi; Billah, Syed Muhammad Baqui; Saquib, Juliann; AlMazrou, AbdulRahman; et al.
Highlights: 5% of Saudi adolescents (grade 7–12) were addicted to gaming. 11% were suffering from a high level of stress. Gaming addiction was strongly associated with moderate- and high-level stress. Abstract: Introduction: Adolescents (age: 10–19 years) make up 15% of the Saudi population and have easy access to electronic gadgets and the Internet, yet data on gaming addiction among adolescents are negligible. We aimed to determine the prevalence of gaming addiction and its association with stress among Saudi school students. Methods: In this cross-sectional survey, 2675 school students (grades 7–12) from 40 randomly selected schools in four main cities of Al-Qassim province in Saudi Arabia participated. The questionnaire inquired about demography, lifestyle, gaming addiction (7-item Game Addiction Scale), and stress (10-item Perceived Stress Scale). Multinomial logistic regression assessed the association between gaming addiction (yes, no) and stress (high, moderate, low). Results: Participants' mean age was 16.1 (SD = 1.6) years; 50% were female; 64% reported >3 h of daily screen time; 5% were addicted to gaming; 11.4% had high-level stress. Addiction to gaming was strongly associated with stress in the adjusted analysis (moderate OR = 6.7, 95% CI = 2.9–15.5; high OR = 11.9, 95% CI = 4.7–30.1). Additionally, those who were older, female, had poor grades, unhealthy dietary habits, an inactive lifestyle, and smoked were more likely to experience high stress. Conclusions: Gaming addiction is strongly associated with stress among Saudi adolescents.